Controlled Surface Segregation Leads to Efficient Coke‐Resistant Nickel/Platinum Bimetallic Catalysts for the Dry Reforming of Methane. Issue 5 (3rd February 2015) - Li, Lidong; Zhou, Lu; Ould‐Chikh, Samy; Anjum, Dalaver H.; Kanoun, Mohammed B.; Scaranto, Jessica; Hedhili, Mohamed N.; Khalid, Syed; Laveille, Paco V.; D'Souza, Lawrence; Clo, Alain; Basset, Jean‐Marie
Abstract Surface composition and structure are of vital importance for heterogeneous catalysts, especially for bimetallic catalysts, which often vary as a function of reaction conditions (known as surface segregation). The preparation of bimetallic catalysts with controlled metal surface composition and structure is very challenging. In this study, we synthesize a series of Ni/Pt bimetallic catalysts with controlled metal surface composition and structure using a method derived from surface organometallic chemistry. The evolution of the surface composition and structure of the obtained bimetallic catalysts under simulated reaction conditions is investigated by various techniques, which include CO‐probe IR spectroscopy, high‐angle annular dark‐field scanning transmission electron microscopy, energy‐dispersive X‐ray spectroscopy, extended X‐ray absorption fine structure analysis, X‐ray absorption near‐edge structure analysis, XRD, and X‐ray photoelectron spectroscopy. It is demonstrated that the structure of the bimetallic catalyst is evolved from Pt monolayer island‐modified Ni nanoparticles to core–shell bimetallic nanoparticles composed of a Ni‐rich core and a Ni/Pt alloy shell upon thermal treatment. These catalysts are active for the dry reforming of methane, and their catalytic activities, stabilities, and carbon formation vary with their surface composition and structure.